2016
DOI: 10.1071/bt15156
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure and development of Paspalum vaginatum (Poaceae): an architectural approach

Abstract: Paspalum vaginatum Sw. is a perennial grass originating from tropical and subtropical regions worldwide that plays important ecological and utilitarian roles such as dune stabilisation and erosion control, and is used as a lawn and forage plant. The vegetative morphology of shoots was studied using an architectural approach with the aim of identifying constant features that characterise the architectural unit of this species, describing its developmental dynamics, and exploring the morphological basis of its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Plants were obtained by vegetative division of one individual (genet) of each genotype, taking advantage of the characteristic clonal growth of this species (Rua & Gróttola 1997). Details about collection place and propagation method are provided in Fabbri et al (2016b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants were obtained by vegetative division of one individual (genet) of each genotype, taking advantage of the characteristic clonal growth of this species (Rua & Gróttola 1997). Details about collection place and propagation method are provided in Fabbri et al (2016b).…”
Section: Methodsmentioning
confidence: 99%
“…In a detailed architectural analysis of two accessions of P. vaginatum, a wild genotype and a commercial cultivar (Fabbri et al 2016b), showed that qualitative morphological characters were constant regardless the genotype. They share similar architectural pattern as they produce stems with different orientation: orthotropic, plagiotropic stoloniferous and plagiotropic rhizomatous.…”
Section: Introductionmentioning
confidence: 99%